Contrasting co‐occurrence patterns of photobiont and cystobasidiomycete yeast associated with common epiphytic lichen species. Issue 5 (13th March 2020) - Mark, Kristiina; Laanisto, Lauri; Bueno, C. Guillermo; Niinemets, Ülo; Keller, Christine; Scheidegger, Christoph
Summary: The popular dual definition of lichen symbiosis is under question with recent findings of additional microbial partners living within the lichen body. Here we compare the distribution and co‐occurrence patterns of lichen photobiont and recently described secondary fungus (Cyphobasidiales yeast) to evaluate their dependency on lichen host fungus (mycobiont). We sequenced the nuclear internal transcribed spacer (ITS) strands for mycobiont, photobiont, and yeast from six widespread northern hemisphere epiphytic lichen species collected from 25 sites in Switzerland and Estonia. Interaction network analyses and multivariate analyses were conducted on operational taxonomic units based on ITS sequence data. Our study demonstrates the frequent presence of cystobasidiomycete yeasts in studied lichens and shows that they are much less mycobiont‐specific than the photobionts. Individuals of different lichen species growing on the same tree trunk consistently hosted the same or closely related mycobiont‐specific Trebouxia lineage over geographic distances while the cystobasidiomycete yeasts were unevenly distributed over the study area – contrasting communities were found between Estonia and Switzerland. These results contradict previous findings of high mycobiont species specificity of Cyphobasidiales yeast at large geographic scales. Our results suggest that the yeast might not be as intimately associated with the symbiosis as is the photobiont. Abstract : See also the Commentary on this article by Hawksworth & Grube, 227 : 1281–1283 .